2020
DOI: 10.1186/s12894-020-00606-5
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic combined intrarenal surgery in the prone-split leg position for successful single session removal of an encrusted ureteral stent: a case report

Abstract: Background: The most serious complication of ureter stent is long-term retention of ureteral stent and stone formation around the stent. Case presentation: A 51-year old female patient with left ureteral stent placed 2 years before developed both pyelic and vesical stones on the two ends of the double J was admitted to our hospital. Intravesical lithotripsy, retrograde ureteroscopy, and percutaneous nephrolithotripsy were performed with the patient in the prone splitleg position. All the stones and the uretera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…This technique also minimizes the possibility of over-dilatation of tract due to direct visual examination from the flexible URS. Moreover, kidney tissues injury caused by too deep penetration and bleeding can also be avoided in this approach [ 2 ]. Although this procedure used many equipment and may affect the higher cost, we think that this procedure should be done in complex kidney stone.…”
Section: Introductionmentioning
confidence: 99%
“…This technique also minimizes the possibility of over-dilatation of tract due to direct visual examination from the flexible URS. Moreover, kidney tissues injury caused by too deep penetration and bleeding can also be avoided in this approach [ 2 ]. Although this procedure used many equipment and may affect the higher cost, we think that this procedure should be done in complex kidney stone.…”
Section: Introductionmentioning
confidence: 99%
“…In one report, the distal end of encrusted ureteral stents was straightening in the bladder without and pull it out of the urethra, then crush calculi around the stent by the ureteroscope with laser, then pull out the double‐J stent and remove whole double‐J stent as one 2 . Another report demonstrated that they successfully removed encrusted ureteral stents by retrograde ureteroscopy and percutaneous nephrolithotripsy 3 …”
mentioning
confidence: 99%